2011
DOI: 10.1007/s13404-011-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle/double-walled carbon nanotube-modified glassy carbon electrode and its application

Abstract: A sensor based on gold nanoparticle/doublewalled carbon nanotube-modified glassy carbon electrode is prepared. Electrochemical behavior of dopamine hydrochloride at gold nanoparticle/double-walled carbon nanotube-modified glassy carbon electrode is investigated. A simple, sensitive, and inexpensive method for determination of dopamine hydrochloride is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…It is noticeable that the estimated Rct values vary inversely with the ks parameter, something which is in absolute agreement with previous studies reported in literature [45,46]. The results demonstrate the fewer barriers for electron transfer, and thus, the greater electrocatalytic activity of carbon nanotubes modified with AuNPs [47,48].…”
Section: Electrochemical Response Of B-supporting
confidence: 91%
“…It is noticeable that the estimated Rct values vary inversely with the ks parameter, something which is in absolute agreement with previous studies reported in literature [45,46]. The results demonstrate the fewer barriers for electron transfer, and thus, the greater electrocatalytic activity of carbon nanotubes modified with AuNPs [47,48].…”
Section: Electrochemical Response Of B-supporting
confidence: 91%
“…The functional groups such as −COOH, −OH, and AuNP etc. of the modified electrode influence the rate of the electrode process .…”
Section: Resultsmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) have recently drawn great interest in biosensor development because they are biocompatible and inert [10]. AuNPs have been employed to amplify signals by forming a nanoparticle ensemble substrate on electrode, thereby increasing the amount of immobilized probe DNA on the electrode surface [11]. AuNPs are also extensively used as labels because each AuNP can provide thousands of electrochemically detectable elements either by itself [12] or as a carrier for enzymes to produce electroactive materials [13].…”
Section: Introductionmentioning
confidence: 99%